1995
DOI: 10.1002/bdd.2510160903
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three H2 receptor antagonists on the disposition of cyclosporin a in the in situ perfused rat liver model

Abstract: The in situ perfused rat liver model was used to investigate the effect of three H2 receptor antagonists on the disposition of cyclosporin A (CyA) and the major human metabolite, AM1. Perfusion experiments, using standard techniques, were carried out on four groups (one control and three H2-receptor antagonist-treated groups) of male Sprague-Dawley rats (300-350 g). All animals received CyA, 2.5 mg; the three treated groups received cimetidine (8 mg), ranitidine (3 mg), or famotidine (0.4 mg). Perfusate and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…The fact that we did not see a delay is consistent with results of other studies in which investigators have reported a lack of interaction between CyA and H 2 -receptor antagonists. 15,[17][18][19] In contrast, however, we saw a steeper slope (higher β 2 ) for the distribution phase. It is believed that a higher β 2 is unlikely to be a function of the coadministration of cimetidine, because there is not any supporting evidence in the literature that cimetidine increases the rate of elimination of CyA, and the concentration of cimetidine would have been decreasing during this time.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The fact that we did not see a delay is consistent with results of other studies in which investigators have reported a lack of interaction between CyA and H 2 -receptor antagonists. 15,[17][18][19] In contrast, however, we saw a steeper slope (higher β 2 ) for the distribution phase. It is believed that a higher β 2 is unlikely to be a function of the coadministration of cimetidine, because there is not any supporting evidence in the literature that cimetidine increases the rate of elimination of CyA, and the concentration of cimetidine would have been decreasing during this time.…”
Section: Discussioncontrasting
confidence: 56%
“…Noticeably, our study did not reveal significant changes in maximum concentration or the overall volume of distribution with the coadministration of cimetidine, which is consistent with other studies in which investigators reported a lack of interaction between CyA and H 2 -receptor antagonists. 15,[17][18][19] An explanation for a lack of interaction may be that cimetidine inhibits some forms of P450, whereas it does not inhibit CYP3A4, which has been identified as the specific P450 isoenzyme involved in the metabolism of CyA. 20,21 It has been documented in rats that cimetidine inhibits hepatic CYP2C, a P450 subfamily, with little or no effect on CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because biliary excretion of ranitidine and famotidine is reported as low in humans (Ͻ2.6% of dose) (Klotz and Walker, 1990), unmetabolized ranitidine and famotidine may accumulate in the liver before subsequent efflux back into blood followed by their eventual renal excretion. Studies using rat-isolated perfused liver systems seem to support the uptake and accumulation of H 2 -receptor antagonists by the liver as perfusate concentrations significantly decline over time, indicating efficient liver extraction (Mihaly et al, 1982;Hughes et al, 1995). Ranitidine and famotidine also may compete for hepatic uptake with other organic cations, potentially leading to drug-drug interactions at the level of hepatic uptake.…”
Section: Discussionmentioning
confidence: 98%